2012
DOI: 10.5858/arpa.2011-0190-oa
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload in Allogeneic Hematopoietic Stem Cell Transplant Recipients

Abstract: Hepatic iron overload is commonly identified in hematopoietic stem cell transplant patients and can be accurately diagnosed by liver biopsy. In addition, hepatic iron overload has been identified in patients receiving as few as 25 units of packed red blood cells, with elevated posttransplant serum ferritin levels, and with blood stream infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
12
1
1
Order By: Relevance
“…[3][4][5][6] The cellular and molecular mechanisms behind this association, however, are yet to be clarified. In particular, available data on the role of ferritin and iron metabolism during the pathophysiology of acute graft-versus-host disease (GvHD), a major contributor to NRM, are scarse.…”
mentioning
confidence: 99%
“…[3][4][5][6] The cellular and molecular mechanisms behind this association, however, are yet to be clarified. In particular, available data on the role of ferritin and iron metabolism during the pathophysiology of acute graft-versus-host disease (GvHD), a major contributor to NRM, are scarse.…”
mentioning
confidence: 99%
“…Although several studies have suggested that there may be an association between IO and a poor patient outcome after allo‐SCT, the causality is still not well established. Hyperferritinemia is associated with increased mortality , and variable markers of iron load are associated with post‐transplant infections . The results of studies on the association between IO and GVHD have been controversial .…”
mentioning
confidence: 99%
“…They found that pretransplant serum ferritin levels significantly predicted BSI within the 100-day period after allo-HSCT [1]. A direct correlation between hepatic IO and BSI was demonstrated in a retrospective cohort of 154 allo -HSCT recipients, as patients with hepatic IO tended to experience more frequent and prolonged episodes of lethal BSI [53]. Altes et al reported a ferritin level above 1500 μg/l was associated with the occurence of bacteremia and febrile days in first 3 months after auto-HSCT [27].…”
Section: Infectionsmentioning
confidence: 97%
“…Liver iron content exceeding 80 mcmol/g of liver dry weight was found to be consistent with IO with a hepatic index greater than 1, 9 mmol/kg/year. However, the need for a relatively large volume of tissue as well as its invasive nature has made this procedure less appealing to most clinicians and patients [4,9,53]. Although liver biopsy is an invasive procedure and can not be safely administered in patients with very low platelet counts, a liver biopsy can be advantageous in some HSCT recipients as it can also exclude alternative causes of hepatic dysfunction, such as infections and GVHD.…”
Section: Liver Biopsymentioning
confidence: 99%
See 1 more Smart Citation